Analysis of Carrying Capacity for Settlement Location based on Spatial Planning in East Serang - Sari, Yetti Anita; Permana, Sendi; Kustanrika, Irma Wirantina; Syahrini, Hilda (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
The problem of land conversion for industrial areas is a phenomenon that occurs in many cities, including East Serang. This phenomenon is a reference in the importance of calculating carrying capacity, settlement capacity and projecting settlement land needs until 2045. The research is located in part of the East Serang area in the settlement spatial pattern, with the research objective: a) analyzing land capacity, b) analyzing the carrying capacity and settlement capacity, and c) determining the distribution of locations that have high carrying capacity and settlement capacity. The approach of this research is quantitative with technical analysis: a) processing through mapping software, b) determination of land capability scale, and c) calculation of carrying capacity and settlement capacity. The results of the research show that: a) the ability class of the East Serang area in the settlement spatial pattern is divided into two, namely medium and high development ability, b) carrying capacity and settlement capacity in the research areas can still be developed into research locations, and c) areas that have high carrying capacity and settlement capacity, namely Kopo and Pamarayan sub district.